Malaysian public sector employees' gold investment intention as a mediator in gold investment behaviour - A. R., Husniyah; A. W., Ahmad Fauzi; S., Mohamad Fazli; O., Mohd. Amim (Malaysian Consumer and Family Economics Association, 2022)
One strategy to increase income among households is through investment. The financial and economic well-being of households among investors may increase due to their decisions. Investment in gold is one attractive investment due to its stability in an uncertain economy. This study applied the Theory of Planned Behaviour and included the gold investment knowledge factor. The potential factors, such as financial risk tolerance, gold investment knowledge, attitude, subjective norms, perceived behavioural control, and intention, are determined by their significance of influence on gold investment behaviour. Multi-stage random sampling was used to select urban public sector employees in Peninsular Malaysia, and 403 respondents responded to a self-administered questionnaire. A structural equation modelling analysis revealed that gold investment attitudes and perceived behavioural control significantly influence employees’ gold investment behaviour through the intention to invest in gold. Hence, gold investment intention mediates the influence of attitudes and perceived behavioural control. Meanwhile, gold investment subjective norms, gold investment intention, and employees’ financial risk tolerance directly influence gold investment behaviour. However, gold investment knowledge does not significantly influence gold investment intention or behaviour. These influential factors on gold investment are information that may be included in programme development to improve employees’ financial well-being. In conjunction with this study, future research may focus on other groups of investors. Studies may also include product characteristics such as perceived risk and perceived use, and trust in others, as the potentially influential factors of gold investment.